PENGARUH MANAJEMEN LABA, KUALITAS AUDIT, KEPEMILIKAN INSTITUSIONAL DAN UKURAN PERUSAHAAN TERHADAP AGRESIVITAS PAJAK (studi empiris pada perusahaan Manufajtur sub Sektor Makanan dan Minuman yang terdaftar di BEI tahun 2014-2016) - Rahmi Ilyani; Azwir Nasir; Al Azhar L (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to examine the effect of earnings management, audit quality, institutional ownership, and firm size to tax aggressiveness(Empirical study on Manufacturing Companies Food and Beverage Sub Sector Listed on Indonesia Stock Exchange During the period 2013-2016. This research uses purposive sampling that is population which used as sample in research is population which fulfill sample criteria. From the criteria, 10 sample of food and beverage sub-sector in Indonesia Stock Exchange in 2013-2016 is obtained. While the data analysis techniques to test the hypothesis using multiple linear regression approach using SPSS version 22.00 for windows. From the results of tests that have been done, simultaneous regression test (Test F) shows that all independent variables studied have simultaneous influence on tax aggressiveness variables. The partial regression test (t test) shows that the audit quality variable partially has significant negative effect on tax aggressiveness. While the variables of earnings management, institutional ownership, and firm size have no effect on tax aggressiveness. The result of coefficient of determination R2 find that 30,7% from independent variable in this research able to influence dependent variable, while the rest 69,3% influenced by other variable not examined in this research.Keywords : Earnings Management, Audit Quality, Institutional Ownership, Firm Size, and Tax Aggressiveness.